Development of eco-friendly products from local raw materials animal husbandry in the Southern Aral Sea region - Saparova G. B. (Zien Journals, 2024)
The paper describes the problem of the influence of environmental conditions on the health of the population. The solution to this problem is the use of natural raw materials. The region has sufficient conditions for the development of the livestock industry. The most promising in this regard are milk and dairy products of various animals common in the region
Keywords: ecology; factors; animal husbandry; camel